Phototherapy as an alternative in the treatment of chronic spontaneous urticaria - Giustozzi, María Inés; Torre, Ana Clara; Ritchie, Carla; Parisi, Claudio Alberto Salvador (Frontiers in Allergy, 2024)
Chronic spontaneous urticaria (CSU) is defined as the occurrence of hives, angioedema, or both, lasting for more than 6 weeks. The treatment is based on the use of antihistamines, omalizumab, and/or cyclosporine following a stepwise algorithm recommended by international guidelines with a high level of evidence. Nevertheless, management can be challenging as some patients do not respond to the suggested drugs or have difficulties accessing them for various reasons. In such cases, phototherapy has been reported as a potential treatment option. The evidence on the effectiveness of phototherapy is limited. Most studies have methodological limitations and involve small numbers of patients. A systematic review and meta-analysis of four studies in 2020 concluded that, despite the limited number of randomized controlled trials and the low level of evidence, considering overall efficacy, risk/benefit balance, and costs, narrow band ultraviolet B therapy (NB-UVB) may be a useful adjunct therapy for CSU. Other studies have suggested that the effectiveness of combined antihistamine and phototherapy appears to be more effective than antihistamine alone, although this is based on very low-quality evidence. Additionally, the risk of recurrence was lower with the combination therapy. The objective of this review was to evaluate the role of phototherapy in the treatment of CSU. While randomized studies with a larger number of participants providing a high level of evidence are still needed, we consider phototherapy to be a valuable tool in specific clinical contexts, such as a bridge to the initiation of other medications or until spontaneous remission of the condition occurs.